Evaluasi Pertumbuhan dan Kadar Pati Beberapa Klon Ubikayu (Manihot esculenta Crantz) - Rosa Nintania; Kukuh Setiawan; Erwin Yuliadi; Muhammad Syamsoel Hadi (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
One way to increase the production and productivity of cassava is using superior varieties. Superior varieties play an important role in increasing the production and productivity of cassava. The assembly of new superior varieties can be done through plant breeding. This research aims to evaluate the growth and yield of cassava in various new clones. This research began in March 2018 at the Integrated Field Laboratory and Agronomy Laboratory, Faculty of Agriculture, University of Lampung. This research was arranged using a complete randomized block design (RAKL) that consist of 6 treatments and 2 replications. The treatments are clones of Huaybong, Waxy, Melati, Kuning, Ketan, and Manalagi. The variables observed in this research are plant height, the number of leaves, total weight of root, starch content, and sianide acid. The results shows that the highest plant is Waxy clone plant height 225.65 cm while Kuning clone is the lowest plant heighest with 142.20 cm. The highest number of leaves is Waxy as 331.67 no while the lowest is Huaybong as109.08. Waxy has the highest number of root as is 8 and the least is Melati clone which is 4. The highest root weight is Kuning clone which is 26.2 kg while the lowest one is Melati clone as 8.13 kg. The highest starch content is Waxy as12.72% and the lowest is Kuning clones as 5.72%. Then the highest HCN content is Waxy clone as 0.07 mg/g and the clones that shows low starch content are Kuning, Manalagi, Ketan and Melati which are 0.02 mg/g.